171 Young Scholar Presentation: Dietary supplementation of Bacillus subtilis influenced intestinal health and metabolomic profiles of weaned pigs experimentally infected with a pathogenic E. coli. (30th November 2020) - Kim, Kwangwook; He, Yijie; Xiong, Xia; Ehrlich, Amy; Li, Xunde; Raybould, Helen; Atwill, Edward Robert; Maga, Elizabeth; Jørgensen, Jens; Liu, Yanhong
Abstract: There is growing evidence to support the beneficial effects of supplementing direct-fed microbials (DFM) on performance, health status, and immune responses of weaned pigs. Therefore, the objective of this study was to investigate dietary supplementation of Bacillus subtilis (DSM 25841) on growth performance, diarrhea, gut permeability, immunity and metabolomic profiles of weaned pigs experimentally infected with a pathogenic F18 Escherichia coli (E. coli). E. coli infection reduced (P < 0.05) growth performance and intestinal villi height, whereas increased (P < 0.05) diarrhea and permeability in the jejunum compared with non-challenged control. Supplementation of Bacillus subtilis linearly enhanced average daily gain of E. coli infected pigs (d 0 to 5 post-inoculation (PI), P < 0.05; d 0 to 11 PI, P = 0.058). Inclusion of high dose Bacillus subtilis reduced (P < 0.05) jejunal permeability on d 5 and d 11 PI compared with the E. coli challenged control. E. coli challenged control pigs up-regulated (P < 0.05) the mRNA expression of SLC5A10 and MUC2 on d 5 PI, but down-regulated (P < 0.05) expression of SLC5A10, MUC2, and CLDN1 on d 11 PI in jejunal mucosa. Supplementation of Bacillus subtilis linearly up-regulated (P < 0.05) the mRNA expression of CFTR and ZO1 on d 5 PI and SLC5A10 and MUC2 on d 11 PI in jejunal mucosa of E. coli infected pigs. E. coli infection increased (P < 0.05) the mRNA expression of several immune genes in the ileal mucosa, while inclusion of Bacillus subtilis linearly down-regulated gene expression of IL1A on d 5 PI (P = 0.07) and IL6 on d 11 PI (P < 0.05) in ileal mucosa of E. coli infected pigs. Supplementation of Bacillus subtilis modified (Fold change > 1.5; FDR < 0.20) metabolomic profiles in colon digesta, related to pathogenesis and amino acid metabolism. In conclusion, supplementation of Bacillus subtilis enhanced growth rate, improved gut health, and modified metabolomic profiles of weaned pigs experimentally infected with a pathogenic E. coli.